Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pengunjung Di Lafayette Coffee Kota Malang - Ahmad Pratama Tri Putra; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study focuses on visitors who visit Lafayette Coffee, based on the results of research conducted by distributing questionnaires to visitors, namely as many as 87 respondents, so some descriptions of the characteristics of the respondents can be taken. The data source used in this study is primary data which is data from the first source or research source data obtained directly from the original source (not through intermediary media). The method used in this research is data collection method data analysis method,Service quality is a level of excellence in meeting customer desires. This shows that the higher the quality of service obtained by visitors, the visitor satisfaction will increase. Service means how far the reality and expectations of customers differ from the service they receive. Service quality can be identified by comparing customer perceptions of the service they actually receive. If the service quality is good, visitors will make a decision to repurchase the product.This shows that the more competitive the prices offered by Lafayette Coffee, the more visitor satisfaction will increase. Price seen from the buyer's point of view, is often used as an indicator of value when the price is related to the perceived benefits of an item or service, price is the amount of money exchanged by customers to obtain the benefits of having or using a product or service. Keywords: Service Quality, Visitor Satisfaction